HMGCR: a malignancy hub - frontiers in cancer diagnosis and therapy - Yang, Yisong; Liu, Yiting; Zou, Teng; Liu, Jiazhuo; Zhou, Xingzhi; Tao, Ran; Liu, Shuangping (Frontiers in Oncology, 2025)
Cholesterol metabolism is significantly activated during most tumor growth. As a key rate-limiting enzyme in cholesterol synthesis, HMG-CoA reductase (HMGCR) affects tumor metabolic reprogramming by upregulating cholesterol metabolism and promotes tumor growth and immune escape by remodeling the tumor microenvironment. It fuels tumor growth by providing cholesterol and isoprenoids, regulating critical pathways (Hippo, Hedgehog, MAPK), and modulating ferroptosis sensitivity. A complex bidirectional relationship exists between HMGCR and the pro-inflammatory cytokine TNF-α: TNF-α can inhibit HMGCR activity and thus inhibit cholesterol synthesis. At the same time, HMGCR influences TNF-αmediated inflammation and immune evasion. Statins, as HMGCR inhibitors, have shown anti-tumor effects in experiments. However, clinical application faces challenges including highly toxic concentration, drug resistance and tissue specificity. Accordingly, further exploration of mechanism-based targeted precision therapies to intervene in the HMGCR-TNF-α axis and related pathways, as well as the development of novel HMGCR inhibitors or optimization of existing drugs, represents an innovative strategy to enhance cancer treatment efficacy and advance drug development.